2020
DOI: 10.4300/jgme-d-20-00122.1
|View full text |Cite
|
Sign up to set email alerts
|

Rural Workforce Years: Quantifying the Rural Workforce Contribution of Family Medicine Residency Graduates

Abstract: Background Rural regions of the United States continue to experience a disproportionate shortage of physicians compared to urban regions despite decades of state and federal investments in workforce initiatives. The graduate medical education system effectively controls the size of the physician workforce but lacks effective mechanisms to equitably distribute those physicians. Objective We created a measurement tool called a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 30 publications
(32 reference statements)
0
22
0
Order By: Relevance
“…26 However, as residency training is not required for dentists as it is with physicians and podiatrists, the "if you build it, they will come" strategy may have different outcomes for this workforce compared with the physician workforce, in which evidence has demonstrated that future practice locations are associated with the location of GME. 4,27 The residency requirement difference may also be a contributing factor associated with the state-by-state variation in dental and podiatry positions and related Medicare GME support, with 6 states receiving no dental or podiatry GME support, and the remaining states and territories and the District of Columbia receiving GME payments per person by state, territory, or district population that ranged from $0.05 to $14.24. However, interest in dental residency programs is strong.…”
Section: Discussionmentioning
confidence: 99%
“…26 However, as residency training is not required for dentists as it is with physicians and podiatrists, the "if you build it, they will come" strategy may have different outcomes for this workforce compared with the physician workforce, in which evidence has demonstrated that future practice locations are associated with the location of GME. 4,27 The residency requirement difference may also be a contributing factor associated with the state-by-state variation in dental and podiatry positions and related Medicare GME support, with 6 states receiving no dental or podiatry GME support, and the remaining states and territories and the District of Columbia receiving GME payments per person by state, territory, or district population that ranged from $0.05 to $14.24. However, interest in dental residency programs is strong.…”
Section: Discussionmentioning
confidence: 99%
“…26 Future federal training investments should be targeted toward programs or other innovative place-based alternatives to traditional GME funding that yield a high return on investment in rural communities. 3,4 An example would be increased and long-term funding for the THC program that is not dependent on Congressional appropriations.…”
Section: Recommended Actionmentioning
confidence: 99%
“…3 While many factors affect the supply and distribution of physicians, graduate medical education (GME) funding is a major determining factor. [4][5][6] According to the Congressional Research Service, ''the size of the federal investment in GMEestimated at $16 billion in 2015-makes it a policy lever often considered to alter the health care workforce and impact health care access.'' 7 Unfortunately, the current distribution of GME funds do not align with rural workforce needs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Place-based training has demonstrated favorable workforce outcomes for rural practice, for example, as evidenced by the outcomes of 1+2 Rural Training Tracks (RTTs). 8,9 Training With and For Rural Communities Community competence in family medicine is grounded in the effectiveness of primary care. Evidence for this is perhaps best recognized in the work of Barbara Starfield's four "Cardinal C's of Primary Care."…”
Section: Commentarymentioning
confidence: 99%